The historical experience of creating administrative centers for national autonomies: the foundation and development of the city of Mikoyan-Shahar (1926-1943) - Zaven V. Akopyan (Кавказология, 2023)
In the history of national-state construction in the 1920s and 1930s, almost all autonomies and other large territorial units already had cities with the status of administrative centers and capitals. All of them existed long before the establishment of Soviet power, and they were dominated by a population that did not belong to the titular nation of the corresponding autonomous republic or region. The only exception was the Karachay Autonomous region, formed in 1926, on the territory of which there was not a single settlement suitable for an administrative center. The author of the article gives a set of reasons that became the basis for the decision to build a new city with the name Mikoyan-Shahar (present-day Karachayevsk). At the present stage, the same situation has developed with the Ingush Republic. Thanks to the support of the federal center, the construction of a new capital, the city of Magas, has begun for this republic.